Effect of education on the incidence rate of occupational exposure resulting from sharp bodies and mucocutaneous contamination with blood and body fluids of patients among nursing personnel of Valiasr Hospital- Fassa, 2008 Efecto de la educación en la tasa de incidencia de exposición ocupacional por objetos cortopunzantes y por contaminación mucocutánea con sangre y fluidos corporales en enfermeros del hospital de Valiasr-Fassa Efeito da educação na taxa de incidência de exposição ocupacional por objetos perfurantes e por contaminação mucocutânea com sangue e fluidos corporais em enfermeiros do hospital de Valiasr-Fassa - Fariba Ghodsbin; Mostafa Bijani; Hashem Rahmati; Zinat Mohebbi; M Kamali (Universidad de Antioquia, 2011)
Objective. To determine the effect of education on the incidence rate of occupational exposure resulted from sharp bodies and mucocutaneous contamination with blood and body fluids of patients among nursing personnel of Valiasr Hospital- Fassa, 2008. Methodology. Interventional study. Samples consisted of 120 nurses (60 as study group and 60 as control group) selected by systemic randomized allocation. The study group was trained in occupational exposure for a period of ten hours. The data collecting tool was an occupational exposure questionnaire that was completed for both groups, before and two months after education. A knowledge test was also applied to both groups before and after education. Data analysis was done by descriptive statistics, frequency, mean and standard deviation, inferential statistics, x², T-test and paired t, and a level of significance p<0.05 was statistically accepted. Results. Results of the research, indicated an increase of the knowledge level and a reduction of the incidence rate of occupational exposure among the study group in such a way that, the knowledge mean score of this group went from 8.1 before education to 14.1 after education (p<0.05). The incidence rate of occupational exposure resulting from sharp bodies and mucocutaneous contamination with blood and body fluids of patients was also reduced after education in the case group (p<0.05). Conclusion. The results of the study indicated improvement of knowledge and practice level in the the case group, concerning occupational exposure due to sharp bodies and mucocutaneous contamination with blood and body fluids of patients after the training intervention. In addition, continuous education in this respect is necessary because its effect lowers with time-lapse. Objetivo. Determinar el efecto de la educación en la tasa de incidencia de exposición ocupacional por objetos cortopunzantes y por contaminación mucocutánea con sangre y fluidos corporales en enfermeros del Hospital de Valiasr en Fassa (Irán) en 2008. Metodología. Estudio de intervención. Se tomó una muestra de 120 enfermeros (60 en el grupo de estudio y 60 en el grupo control) asignados por aleatoriazación sistemática. El grupo de estudio recibió 10 horas de capacitación en prevención de exposición ocupacional. Para la recolección de datos se utilizó un cuestionario, el cual fue completado por ambos grupos antes y dos meses después de la capacitación, igualmente se aplicó un examen de conocimientos a ambos grupos antes y después de la capacitación. Resultados. Los resultados del estudio indicaron aumento del nivel de conocimiento y disminución de la tasa de incidencia de exposición ocupacional en el grupo de estudio de tal manera que el puntaje de la media del nivel de conocimiento de este grupo alcanzó un puntaje de 8.1 antes de la capacitación a 14.1 después de la capacitación, (p<0.05). Conclusión. El programa educativo se asoció a mejores prácticas preventivas del riesgo de exposición a objetos cortopunzantes y contaminación mucocutánea con sangre y fluidos corporales de pacientes. Objetivo. Determinar o efeito da educação na taxa de incidência de exposição ocupacional por objetos perfurantes e por contaminação mucocutânea com sangue e fluidos corporais em enfermeiros do Hospital de Valiasr em Fassa (Irã) em 2008. Metodologia. Estudo de intervenção. Tomou-se uma mostra de 120 enfermeiros (60 no grupo de estudo e 60 no grupo controle) atribuídos por escolha aleatória sistemática. O grupo de estudo recebeu 10 horas de capacitação em prevenção de exposição ocupacional. Para a recolha de dados se utilizou um questionário, o qual foi completado por ambos os grupos antes e dois meses depois da capacitação igualmente se aplicou um exame de conhecimentos a ambos os grupos antes e depois da capacitação. Resultados. Os resultados do estudo indicaram aumento do nível de conhecimento e diminuição da taxa incidência de exposição ocupacional no grupo de estudo de tal maneira que a pontuação da média do nível de conhecimento deste grupo atingiu uma pontuação de 8.1 antes da capacitação a 14.1 depois da capacitação, (p<0.05). Conclusão. O programa educativo se associou a melhores práticas preventivas do risco de exposição a objetos perfurantes e contaminação mucocutânea com sangue e fluidos corporais de pacientes.